The adventures of Tom Sawyer (The Mark Twain in Person Audio Library, ,, 2012)
"Mark Twain's classic The Adventures of Tom Sawyer has been enjoyed by generations of readers across the world since its publication in 1876. With its humorous glimpses into life in nineteenth-century, small-town America, this novel has provided unique social commentary that continues to be discussed in classrooms today. Tom Sawyer, a mischievous boy growing up in the fictional town of St. Petersburg, Missouri, is constantly getting in and out of trouble with his friend Huckleberry Finn. Based on Twain's own childhood, this novel not only gives profound insights into American life but also shows how children can develop moral codes based on friendship, loyalty, and respect"--
15 copies of the audiobook.

Tom Sawyer (Lifetime library, ,, 1996)
A captivating retelling of Mark Twain's classic adventure story. True to the original in plot, character, themes and style, this is an excellent way for a young reader to meet Tom Sawyer for the first time. Tom Sawyer is a respectable boy in a little Mississippi River town. Huck Finn is a freedom-loving, neglected outcast. What better playmate could Tom want? One night, innocent games of pirates and Robin Hood turn serious when the boys witness a murder in the graveyard. The murderer will kill them if they tell the truth. What should they do? The boys decide to search for the murderer's treasure. What risks will they take? Who else will they endanger? Will they have the courage and quick-thinking to escape from dark caverns, cross the mighty Mississippi, and out with the criminals? Will they find what they are looking for?

The adventures of Huckleberry Finn (Classic collection), ,, 2011)
Called "the veriest trash" by a member of the Concord, Massachusetts Library Board that banned the novel when it was first published, Huckleberry Finn has come to be viewed, as H.L. Mencken put it, as "one of the great masterpieces of the world." Ernest Hemingway wrote that "All modern American literature comes from one book by Mark Twain called Huckleberry Finn....There was nothing before. There has been nothing as good since." A daringly ironic attack on racism American-style, Twain's story of what he once called a "sound heart" triumphing over a "deformed conscience" is poignant, powerful, and fresh. It is no wonder that this extraordinary book continues to captivate readers around the world. This handsome Oxford World's Classic edition uses the reliable 1885 text and includes in-depth, up-to-date editorial apparatus
Discover Moses and the bulrushers , Our gang's dark oath , We ambuscade the A-rabs , Hair-ball oracle , Pap starts in on a new life , Pap struggles with the Death Angel , I fool Pap and get away , I spare Miss Watson's Jim , House of death floats by , What comes of handlin snake-skin? , They're after us! , "Better let blame well alone" , Honest loot from the "Walter Scott" , Was Solomon wise? , Fooling poor old Jim , Rattlesnake-skin does its work , Grangerfords take me in , Why Harney rode away for his hat , Duke and the Dauphin come aboard , What royalty did to Parkville , Arkansaw difficulty , Why the lynching bee failed , Orneriness of kings , King turns parson , All full of tears and flapdoodle , I steal the king's plunder , Dead Peter has his gold , Overreaching don't pay , I light out in the storm , Gold saves the thieves , You can't pray a lie , I have a new name , Pitiful ending of royalty , We cheer up Jim , Dark, deep-laid plans , Trying to help Jim , Jim gets his witch pie , "Here a captive heart busted" , Tom writes nonnamous letters , Mixed-up and splendid rescue , "Must 'a' been sperits" , Why the didn't hang Jim , Last. Nothing more to write.

The haunted cabin mystery (Boxcar children, 20, 1, 2014)
The Alden children travel on a Mississippi paddle-wheel steamer to visit an old family friend in his cabin near Hannibal, Missouri, and try to discover who is responsible for the mysterious activities near the house.

The actual & truthful adventures of Becky Thatcher (Dreamscape Media, LLC, Dreamscape Media, Simon & Schuster Books for Young Readers, 2014)
In 1860, eleven-year-old Becky Thatcher, new to St. Petersburg, Missouri, joins the boys at school in a bet to steal from the Widow Douglas in hopes of meeting a promise to have adventures that she made her brother, Jon, before he died.

The Boxcar Children #20: The haunted cabin mystery (Boxcar children, 20, 1, 1991)
The Alden children travel on a Mississippi paddle-wheel steamer to visit an old family friend in his cabin near Hannibal, Missouri, and try to discover who is responsible for the mysterious activities near the house.

The adventures of Tom Sawyer (Adventures of Tom and Huck, ,, 2019)
Presents an adaptation of the classic novel which follows the adventures and pranks of a mischievous, good-natured, boy growing up in a Mississippi River town in the early nineteenth century. Includes review questions.
Tom and the fence , Showing off in sunday school , Tom meets Becky , Heartbreak comes quickly , Tragedy in the graveyard , Tom wrestles with his conscience , Brave Tom , The trial of Muff Potter , Seeking buried treasure , Danger inside the haunted house , On the trail of Injun Joe , Huck's a hero , Trapped in the cave , Joyful news and a great surprise , Respectable Huck joins Tom's gang.

The riverboat phantom (Aladdin, 2009)
Jon and Tania--who can see and communicate with ghosts--journey down the Mississippi River on an antique riverboat in search of ghosts, but the spirit of a pyromaniac, riverboat captain proves dangerous to the siblings and the crew.

Trixie Belden and the Mystery of the Ghostlyt Galleon (Trixie Belden, 15, 1, 2006)
While on a trip to St. Louis, fourteen-year-old Trixie Belden discovers some mysterious papers in her hotel room and soon realizes that she and her friends are being followed as they cruise in a towboat down the Mississippi River.
Promise of adventure , Catfish princess , Good news , Something in the air , Moonlight music , Stowaway , Bob-white luck , Rescued , Early-morning swim , Off to Hannibal , Surprise at Jackson's Island , St. Peter , Aguileras again , New development , On the steamboat , Key , Bob-white! , Reward.

Huckleberry Finn (Real reads, ,, 2010)
"This is a retelling of the adventures of a boy and a runaway slave as they travel down the Mississippi River on a raft in the mid-nineteenth century."--Publisher.